Нотариат Удмуртии: прошлое, настоящее, будущее / [составитель Т. Н. Силина] - Силина Татьяна Николаевна (Удмуртия, 2004)
Экземпляры: (20170406) / Инвентарный номер: 2255 / Цена: / Сис.шифр: 67.76(2Рос.Удм) / Авт.знак: Н 85 / ГРНТИ: 10.71.55 / ББК: 67.76(2Рос.Удм)